Distribution of a Robertsonian translocation in goats - Gonçalves, H. C. [UNESP]; Jorge, W. [UNESP]; Cury, P. R. [UNESP] (Elsevier, 1992)
Two hundred and five animals were cytogenetically studied. They were related to a male goat called 'Harald', imported from Switzerland, who was a t 5 15 chromosomic translocation carrier. 29.27% of the analyzed animals were heterozygous and 4.88% were homozygous. All carrying animals were found in Botucatu, Limeira and São Manuel city in Brazil. Descendants of this buck were sold in several regions of Brazil, and may have spread this aberration. © 1992.